Status, standards, technologies and existing problems of residential ventilation in China. Issue 4 (April 2020) - Fan, Dong-Ye; Wang, Qing-Qin; Zhao, Li; Liu, Mao-Lin
Indoor air pollution level in dwellings varies in different areas. Specifically, the formaldehyde and total volatile organic compound pollution are serious in new residential buildings according to the investigation of indoor air pollution status of residential buildings in China. Appropriate ventilation, as an important means to reduce the concentration of indoor pollutants, is mainly affected by ventilation mode, ventilation performance, ventilation strategies, etc. This paper analyses the status, standards, technologies and products related to residential ventilation and concludes the existing drawbacks in residential ventilation applications in China. Understanding of residential ventilation, and its standards, design methods, technologies, products, also the economy and usability should be given a major consideration to research.